Gopher Frogs, Burrows, and Fire: Interactions in the Longleaf Pine Ecosystem - Elizabeth A. Roznik; Steve A. Johnson (EDIS, 2009)
WEC-250, a 5-page illustrated fact sheet by Elizabeth A. Roznik and Steve A. Johnson, helps land stewards understand the relationships between fire, burrowing animals, and the animals that use burrows, such as the gopher frog. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, February 2009.